PENGEMBANGAN PROGRAM EKOWISATA DI RESORT MANDALAWANGI TAMAN NASIONAL GUNUNG GEDE PANGRANGO KABUPATEN CIANJUR JAWA BARAT - Sudrajat, Iyat; Sunarminto, Tutut; Nitibaskara, TB Unu (Media Konservasi, 2016)
Development of Ecotourism Program at Mandalawangi Resort of Mount Gede Pangrango National Park (TNGGP) is done by optimizing the supply of tourist collaborated with tourist demand. Tourism resource most interesting at Resort Mandalawangi namely Puncak Gunung Gede - Pangrango then others are rare animals such as Leopards java (Panthera pardus) is the key species and Javan Gibbon (Hylobates Molloch) as a flagship species, as well as waterfalls, crater, Blue Lake, and Gayonggong Swamp. Social and cultural potential of a pattern of community life Sundanese-oriented agriculture as well as the existence of the mythical legend of the kingdom in TNGGP. Visitors dominant male, student status with the last education of SMP / MTs, 16-20-year-old, from Bekasi to have the motivation tends to settle for pleasure. Assess visitors tend not to know that TNGGP have ecotourism program that School Visit, Visit to School, Conservation Camp, Local Content Filling Material Environmental Education / Nature Conservation and Environmental Education for Teachers, Farmers, and the Young Generation. The concept of program development of ecotourism in Resort Mandalawangi using the theme "TNGGP, Cultured Conservation Area". This concept will focus on the utilization of resources and nature taking into consideration the safety of visitors as well as integrate with shades of Sundanese culture around tourism area Cibodas. Another aspect that needs to be developed to support the promotion of ecotourism programs, establish Sundanese cultural nuances and supporting infrastructure at KWC, strengthening human resources ecotourism program managers. Keywords: development, ecotourism, potential, program, TNGGP